The Impact of the Plan and PDEODE Strategies in Developing Awareness of Cognitive Processes and Reducing Psychological Pollution Among Students of the Faculty of Physical Education and Sports Sciences - Raed Abdulameer Abbas Al-Mashhadi (Journal of Global Pharma Technology, 2018)
The Research Aims toTo identify the psychological awareness of cognitive processes and pollution of the students of the Faculty of Physical Education and Sports Science.To know the impact of strategies and PDEODE in PLAN Transgender search.Any previous two strategies realized more development in the variables of the students.Use the descriptive approach in the method of normative studies and comparative studies in the measurement of psychological pollution and awareness of cognitive processes, and the experimental method of the two equal groups in the tribal and remote tests in the variable PLAN and PDEODE strategies. And select the community and the research sample students the second phase of the Faculty of Physical Education and Sports Science - University of Babylon in the academic year (2014-2015), was the number of educational units (28) units divided into 14 units at each strategy, by one lecture each week and the number of ( 7) topics for each variable, are executed in the order, and repeated to increase the absorption of interaction and students about the importance of topics in their lives, and after the use of statistical methods were reached conclusions:1.The arithmetic mean of the variables of research within the standard level when the moderate sample.2.The PLAN and PDEODE strategies have an effect on the two search variables.The PLAN strategy has a greater impact than the PDEODE strategy in developing awareness of cognitive processes and reducing psychological pollution among students.Keywords: Strategy PLAN, PDEODE strategy, awareness of cognitive processes, psychological pollution.